Financial risk manager handbook plus test bank : - Jorion, Philippe (J. Wiley & Sons, 2011)
Filled with in-depth insights and practical advice, the Financial Risk Manager Handbook is the core text for risk management training programs worldwide. Presented in a clear and consistent fashion, this completely updated Sixth Edition, mirrors recent updates to the new two-level Financial Risk Manager (FRM) exam, and is fully supported by GARP as the trusted way to prepare for the rigorous and renowned FRM certification. This valuable new edition includes an exclusive collection of interactive multiple-choice questions from recent FRM exams.